2018
DOI: 10.1057/s41599-018-0143-3
|View full text |Cite|
|
Sign up to set email alerts
|

Knowledge management for policy impact: the case of the European Commission’s Joint Research Centre

Abstract: The European Commission's Joint Research Centre (JRC) employs over 2000 scientists and seeks to maximise the value and impact of research in the EU policy process. To that end, its Knowledge management for policy (KMP) initiative synthesised the insights of a large amount of interdisciplinary work on the 'evidence-policy interface' to promote a new skills and training agenda. It developed this training initially for Commission staff, but many of its insights are relevant to organisations which try to combine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
63
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 49 publications
1
63
0
5
Order By: Relevance
“…Researchers are advised to conduct high-quality, robust research (Boyd, 2013;Whitty, 2015;Docquier, 2017;Eisenstein, 2017) and provide it in a way that is timely, policy relevant, and easy to understand, but not at the expense of accuracy (Havens, 1992;Norse, 2005;Simera et al, 2010;Bilotta et al, 2015;Kerr et al, 2015;Olander et al 2017;POST, 2017). Specific research methods, metrics and/or models should be used (Aguinis et al 2010), with systematic reviews/ evidence synthesis considered particularly useful for policymakers (Lavis et al, 2003;Sutherland, 2013;Caird et al, 2015;Andermann et al, 2016;Donnelly et al, 2018;Topp et al, 2018), and often also randomised controlled trials, properly piloted and evaluated (Walley et al, 2018). Truly interdisciplinary research is required to identify new perspectives (Chapman et al, 2015;Marshall and Cvitanovic, 2017) and explore the "practical significance" of research for policy and practice (Aguinis et al 2010).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Researchers are advised to conduct high-quality, robust research (Boyd, 2013;Whitty, 2015;Docquier, 2017;Eisenstein, 2017) and provide it in a way that is timely, policy relevant, and easy to understand, but not at the expense of accuracy (Havens, 1992;Norse, 2005;Simera et al, 2010;Bilotta et al, 2015;Kerr et al, 2015;Olander et al 2017;POST, 2017). Specific research methods, metrics and/or models should be used (Aguinis et al 2010), with systematic reviews/ evidence synthesis considered particularly useful for policymakers (Lavis et al, 2003;Sutherland, 2013;Caird et al, 2015;Andermann et al, 2016;Donnelly et al, 2018;Topp et al, 2018), and often also randomised controlled trials, properly piloted and evaluated (Walley et al, 2018). Truly interdisciplinary research is required to identify new perspectives (Chapman et al, 2015;Marshall and Cvitanovic, 2017) and explore the "practical significance" of research for policy and practice (Aguinis et al 2010).…”
mentioning
confidence: 99%
“…Be 'policy-relevant' (NCCPE, 2018;Maddox, 1996;Green et al, 2009;Farmer, 2010;Kerr et al, 2015;Colglazier, 2016;Tesar et al, 2016;Echt, 2017b;Fleming and Pyenson, 2017;Olander et al, 2017; POST, 2017) (although this is rarely defined). Two exceptions include the advice for research programmes to be embedded within national and regional governmental programmes (Walley et al, 2018) and for researchers to provide policymakers with models estimating the harms and benefits of different policy options (Basbøll, 2018) (Topp et al, 2018).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the construct relies on identifying gaps between policy and academia and assumes that the two communities have a 'lack of fit' (Wehrens, 2014). Furthermore, Topp et al (2018) suggests that the problems identified in the 'lack of fit' between the two communities exist even when the two communities belong to the same organisation and are located in the same building.…”
mentioning
confidence: 99%